The effect of individualism and collectivism on customer satisfaction in retail sector asian versus western culture / Abdul Hamid Abdul Halim, Muhammad Hafizi Zamri and Mohd Faizol Rizal Mohd Rasid - Abdul Halim, Abdul Hamid; Zamri, Muhammad Hafizi; Mohd Rasid, Mohd Faizol Rizal (Faculty of Business and Management and UiTM Press, Universiti Teknologi MARA, Malaysia., 2018)
Customer satisfaction is defined as the customer's attitude towards the perceived service performance, which results from the differences in pre-existing expectations and the actual service performance. There are many factors that can lead to customer satisfaction, but instead of looking into all factors, it is interesting to look at cultural differences since the study focuses on the Malaysian setting, which is known for the multicultural environment. More interestingly, businesses in Malaysia not only involve local customers, but as well as customers from Asian and Western regions. The aims of this study are to determine the relationship between individualism and collectivism towards customer service satisfaction, specifically in the retail sector which involves multinational brands as well as multicultural customers. The use of Geert Hofstede Dimension theory in this study is because it is one of the most important theory in cultural differences studies and has generated a large body of research. A quantitative method has been used and the study has been conducted on 103 respondents, 51.5 % are from Asian origin and 48.5% are of Western origin. Although both individualism and collectivism have a significant impact on customer service satisfaction in the retail sector, it is proven in this study that collectivism has more to do in determining the satisfaction level as a whole. It is recommended that further studies should be done outside of Klang Valley. Furthermore, future research should seek to expand the pool of potential explanatory variables such as how cultural differences factor can help influence customer satisfaction.